Advances in Legumes for Human Nutrition - Johnson, Stuart; Bhattarai, Rewati (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We are very excited to introduce this Special Issue of Nutrients, "Advances in Legumes for Human Nutrition". Recently, legumes have contributed to a sustainable and increased food supply for the rapidly growing global population due to climate change. Legume seeds that are intact or milled into flour offer a complex array of macro- and micronutrients and phytochemicals for human nutrition. Additionally, they can be fractionated into their component proteins, starches, lipids and dietary fibre as health- and techno-functional food ingredients. These ingredients are in great demand by the food industry, for example, in the manufacture of vegetarian and vegan dairy products and meat analogues with good nutritional profiles. However, the issues, such as micronutrient availability, antinutrients and allergenicity, still require solutions for the maximum uptake of legumes by humans. We invited manuscripts that address any aspect of this broad topic, including the impact of innovative food technologies on the nutritional value of legumes and those focusing on nutritional properties of seeds from underutilised members of the Fabaceae (Leguminosae) family.